Uma proposta de sequência de ensino investigativa, em uma perspectiva multimodal, para o ensino dos órgãos dos sentidos. - Mônica dos Santos Cruz (2019)
This research aimed to discuss the potential of a investigative teaching sequence on the theme Organs of Senses and the contribution of the use of semiotic resources to its development. The guiding questions were: does the teaching sequence, proposed to work on the theme sense organs, present observable investigative aspects in the interactions between teacher and students during its development? Is it possible to establish relationships between the intentional use of semiotic resources at times when investigative aspects are triggered during sequence development? Therefore, a teaching sequence with seven activities was built and developed with students of the 8th grade of elementary school aiming to work the theme sense organs in a biological and social perspective. Each proposed activity presented a specific problematization and provided for the use of a semiotic resource such as images, texts, videos and objects. In addition, a general problematization common to the whole sequence has been proposed. The data obtained from the research come from the audio and video recording records of the classes, the teacher / researcher's logbook and student group audio records, from which it was possible to generate general and specific mappings of each class. In the data analysis, we sought to observe the presence of investigative aspects delimited by the researchers from the theoretical framework of the area (Munford and Lima, 2007; Kelly, 2007 and 2014; Carvalho, 2013; Sasseron, 2013 and 2015; Maline, Sá, Maués e Souza, 2018, Solino, Ferraz and Sasseron, 2015; Pedaste, 2015), namely: problematization; hypothesis survey; investigation, argumentation and discussion. Our analyzes allowed us to identify these aspects (individually or together) in all proposed activities, triggered by both the conduct of the activities by the teacher / researcher and the interactions between students in their work groups. We also found that the use of semiotic resources, intentionally inserted in the sequence activities, potentiated the investigation process, since they triggered investigative aspects such as problematization, investigations to test hypotheses and helped in the construction of arguments. We consider that the sequence of teaching developed has investigative potential that collaborates with the learning of the theme and that semiotic modes contributed to its development. For the final education sequence, the educational product of this work, presented in editorial format, the following adjustments were made: the decrease in the amount of activities performed per class, the elaboration of a text with guidance on the way the teacher conducts. ; and changes to the wording of the proposed questions for discussion with the class.